2019
DOI: 10.4314/jae.v23i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of catfish marketing in Egor Local Government Area of Edo State, Nigeria

Abstract: The study examined the characteristics of catfish marketing in Egor Local Government Area of Edo State, Nigeria. Multistage sampling technique was used to select four communities: Isihor, Evbomore, Ekheoba and Odigi. This was followed by random sampling of one central market in each community and fifteen respondents were sampled randomly from each central market in each community giving a total sample size of sixty respondents. Data were analysed using mean, percentages gamma, chi square and Pearson product mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Socioeconomic characteristics of fresh catfish traders in Uvwie In addition, this outcome validates the point that the institution of marriage is still cultivated or cherished. This result is similar to that ofOmoregbee et al (2019), who found that the majority (85%) of catfish traders in the Egor Local Government Area of Edo State were married. Furthermore, this result is also similar to the findings ofNjoku and Offor (2016), who reported that the majority of the catfish traders in Aba South Local Government Area of Abia State were married.…”
supporting
confidence: 88%
“…Socioeconomic characteristics of fresh catfish traders in Uvwie In addition, this outcome validates the point that the institution of marriage is still cultivated or cherished. This result is similar to that ofOmoregbee et al (2019), who found that the majority (85%) of catfish traders in the Egor Local Government Area of Edo State were married. Furthermore, this result is also similar to the findings ofNjoku and Offor (2016), who reported that the majority of the catfish traders in Aba South Local Government Area of Abia State were married.…”
supporting
confidence: 88%